2015
DOI: 10.1128/mbio.02518-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Molecular Cloning, and Analysis of Full-Length Hepatitis C Virus Transmitted/Founder Genotypes 1, 3, and 4

Abstract: Hepatitis C virus (HCV) infection is characterized by persistent replication of a complex mixture of viruses termed a “quasispecies.” Transmission is generally associated with a stringent population bottleneck characterized by infection by limited numbers of “transmitted/founder” (T/F) viruses. Characterization of T/F genomes of human immunodeficiency virus type 1 (HIV-1) has been integral to studies of transmission, immunopathogenesis, and vaccine development. Here, we describe the identification of complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 114 publications
0
22
0
Order By: Relevance
“…The resulting pool of novel viral RNA sequences provides the raw material for natural selection and rapid evolution under pressures that include immune recognition. HCV must evolve within each new host to maximize its potential to replicate and minimize immune-mediated clearance (203209). As HCV infects a new host, viral sequence diversity may initially be limited by a founder effect.…”
Section: T Lymphocytes In Hcv Infectionmentioning
confidence: 99%
“…The resulting pool of novel viral RNA sequences provides the raw material for natural selection and rapid evolution under pressures that include immune recognition. HCV must evolve within each new host to maximize its potential to replicate and minimize immune-mediated clearance (203209). As HCV infects a new host, viral sequence diversity may initially be limited by a founder effect.…”
Section: T Lymphocytes In Hcv Infectionmentioning
confidence: 99%
“…It is estimated that 2.8% of the world population, which corresponds to 185 million people, is living with the chronic form of hepatitis C, and that each year about 350 thousand people die as a result of its complications, such as liver cirrhosis and hepatocellular carcinoma [2, 3]. In Brazil, the prevalence of HCV infection in the general population is 1.3%, with differences among Brazilian regions (from 0.68% in the Northeast to 2.1% in the North); in the Midwest, a prevalence of 1.6% is estimated among individuals over 20 years-old [4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the molecular, biological, and immunopathogenic properties of HCV T/F viruses and their contributions to early virus-host interactions, single-genome sequence (SGS) analyses were conducted to include full-length T/F genomic analyses of HCV, including the 5= and 3= UTR (44). Six subjects from whom a total of 7 unique full-length T/F genomes were inferred on the basis of SGS analyses of the 5= UTR, all structural and regulatory genes, and the X region were previously reported (44). The sequences of these T/F genomes, exclusive of polyU/UC sequences, were unambiguous because, in each case, the plasma vRNA/cDNA sequences conformed to a model of random variation from which a coalescent T/F genome could be inferred.…”
mentioning
confidence: 99%
“…Extensive analysis of polyU/UC sequences from the six acute-infection subjects included sequential sampling and analysis of plasma vRNA throughout the acuteinfection period. Results from these analyses indicated that MuLV reverse transcriptase and, to a lesser extent, Taq polymerase were associated with artificially shortened polyU/UC sequences of T/F genomes (44). HCV RNA-dependent RNA polymerase slippage could also occur but was assumed to contribute less given the known structure-function relationships of this polymerase and its processivity.…”
mentioning
confidence: 99%